ALAM SEBAGAI MEDIA KEHIDUPAN MANUSIA DALAM NOVEL KUBAH DI ATAS PASIR KAJIAN EKOLOGI SASTRA - Armini Arbain (Universitas Andalas, 2020)
This paper aims to describe the relationship of Literary Works (novels) to nature. Literary studies that emphasize the relationship of literature with nature entered into the realm of literary ecology and specifically called Literary Ecocritics. In the presentation of this paper it leads to a descriptive description as a characteristic of qualitative research. The scientific method applied in this study is the discourse approach that exists in eco-criticism. In the novel Kubah di Atas Pasir by Zhainal Fanani, nature is not only used as a setting of place and atmosphere in literary works but also an aspect that helps build the story and aesthetics of a literary work. In this novel, nature is used as a medium of communication by humans in their lives.Keywords: Nature, eco-criticism, media, and literature